PENINGKATAN PRODUKTIVITAS Indigofera sp. SEBAGAI PAKAN HIJAUAN BERKUALITAS TINGGI MELALUI APLIKASI PUPUK ORGANIK CAIR: 1. PRODUKSI HIJAUAN DAN DAMPAKNYA TERHADAP KONDISI TANAH - Suharlina, Suharlina; Abdullah, Luki (Pastura, 2011)
The food flavor manufacture waste (called Sipramin) have a great potential to used as liquid organic fertilizer due to the nutrition contents that needed by plants. The objectives of this research were to evaluate the effect of sipramin as liquid organic fertilizer on soil condition, re-growth, and herbage productivity of Indigofera sp. For ruminants. This experiment used factorial completely randomized design; the first factor was fertilizer dosages (0, 10, 20 and 40%) and the second factor was fertilization times (30 and 15 days before harvested [dbh]). The observed variables were soil chemical and biological characteristic, re-growth and forage production, and nutritive value of Indigofera sp. for ruminants. The data were analyzed by analysis of variance. The result showed that the soil nitrogen, number of phosphate resolvability bacteria and Rhizobium sp. were significantly different (P<0.05) on 40% fertilizer dosage than the other treatments. The phosphate resolvability bacteria and available phosphate (P available) of 15 dbh were higher than 30 dbh. Sipramin fertilizer of 40% dosage improved C-organic content and carbon to nitrogen (C/N) ratio value of soil, and significantly (P<0.01) increased forage production (leaf and steam). The leaf and steam ratio of 15 dbh were higher than 30 dbh. There were significantly different (P<0.01) on number of root nodule on 40% dosage than others. The addition of 40% sipramin at 15 dbh fertilization time showed the best result to chemical and biological soil characteristic, re-growth, and productivity of Indigofera sp.
Keywords: herbage; Indigofera sp.; liquid organic fertilizer; sipramin